김춘수의 무의미시에 나타나는 "의미" - 임경섭; Kyung Seop Lim (인문학연구, 2010)
본 논문은 김춘수의 후기시편들이 집중하고 있는 `무의미`를 주제로 무의미시의 담론적 효과에 대해 분석하는 것을 목적으로 한다. 김춘수가 논의한 `무의미시`란 역사나 현실에 대한 허무의식의 표출의 일환으로 의미나 대상의 형상화를 의도하지 않는 시작과정을 말한다. 그러나 역설적으로 이러한 무의미시의 전략은 오히려 수많은 역사적·시대적 함의를 생산하는 효과를 낳는다. 김춘수에게서 드러나는 `무의미`는 `의미의 부재`를 뜻하는 것이 아니라 정치적이고 권력적인 이데올로기에 의해 고정되는 `의미`를 해체함으로써 이와는 구별되는 `또 다른 의미`를 재생산하는 양상을 보여주고 있다. `무의미`는 의미의 포기가 아니라 언어가 하나의 고정점에 도달하는 것을 적극적으로 지양함으로써 무의미의 순환이라는 구조적인 층위에서의 의미를 겨냥하게 된다. 그것은 한 대상에 고착되지 않는 언어의 의미, 즉 언어와 대상의 간극 사이에 자리하는 실재적 대상을 향한 끊임없는 갈구의 방식으로 구현된다. This study aims at analyzing the discourse effect of nonsense poems focusing on `nonsense` that Kim Chun Soo`s latter poetry concentrates on. His `nonsense` poetry means the writing process, which does not intend to figure meaning and objects to present the nihility about history and the actual. But ironically, this strategy of `nonsense` results in producing various historical and contemporary implications. His `nonsense` does not mean the absence of meaning but another meaning reproduced by deconstructing the meaning fixed by political and ideological power. This is not the abandon of meaning but targetting the circulation of `nonsense`, the meaning in the level of structure through sublating actively one final meaning. It is embodied in the thirsty to the reality in which exists the distance between language and subject exists.